Spontaneous tumour lysis syndrome secondary to the transformation of chronic myelomonocytic leukaemia into acute myeloid leukaemia. (9th March 2016) - Langridge, Alexander; Musgrave, Kathryn; Upadhye, Yogesh
Abstract : A 78-year-old man, with a 6-year history of stable chronic myelomonocytic leukaemia (CMML), presented with general deterioration and worsening pancytopenia. Bone marrow biopsy showed that his disease had transformed into acute myeloid leukaemia (AML). He was started on a supportive transfusion regimen and did not receive any chemotherapy or corticosteroids. Several weeks later, he developed acute renal failure and was admitted to a medical admissions ward. Spontaneous tumour lysis syndrome (sTLS, grade 1) was diagnosed, as per the Cairo and Bishop criteria. He was treated with intravenous fluids, rasburicase and allopurinol. His renal function improved and he recovered from the sTLS. The authors believe that this is the first published case of sTLS occurring as a result of CMML transforming into AML; it highlights the importance of recognising sTLS as a cause of renal failure and electrolyte disturbance before cancer treatment begins.